(untitled) (Experimental biology, 2024)
The work analyzed the content of Parkin (PRKN) and mitofilin (IMMT - Inner mitochondrial membrane transmembrane) proteins in the lung tissue of Wistar rats under the influence of chrysotile asbestos. To reproduce experimental asbestosis, chrysotile asbestos dust was injected intratracheally into the lungs of experimental rats, and saline solution was injected into control animals. The animals were divided into three groups: 1) control; 2) poisoned with asbestos at a dose of 25 mg; 3) poisoned with asbestos at a dose of 50 mg. Two months after asbestos inoculation, the lungs of the rats were removed and homogenized. The content of PRKN and IMMT in homogenates was determined using ELISA. We have shown that under the influence of chrysotile asbestos in the lung tissues of rats, a significant decrease in the levels of the PRKN protein, which controls mitochondrial mitophagy, is observed. The IMMT content in mitochondria of rat lung tissue after exposure to asbestos was lower compared to the control group. Our previously obtained data on the morphometric parameters of mitochondria allowed us to assess the degree of ultrastructural disorders of mitochondria, which may indicate mitochondrial dysfunction under the influence of asbestos. Taken together, these results support a link between damage to mitochondrial structure and defects in the respiratory complex. Taken together, these results support a link between damage to mitochondrial structure and the development of asbestosis.